2019
DOI: 10.3889/oamjms.2019.441
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Knowledge of Soil-Transmitted Helminth Infections in Mandailing Natal, North Sumatera, Indonesia

Abstract: BACKGROUND: Soil-transmitted helminth (STH) infection remains of public health importance, particularly in developing countries. North Sumatra province of Indonesia has reported high prevalences of STH in many of its districts. AIM: In this study, we aimed to determine the prevalence of STH and evaluated STH knowledge and risk behaviours of school children in Mandailing Natal district. METHODS:  We conducted a cross-sectional study in two primary schools in Mandailing Natal district, North Sumatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 8 publications
0
9
0
9
Order By: Relevance
“…A study in North Sumatra found a significant association between wearing shoes and helminthiasis infection (p = 0.004 and prevalence ratio of 3.195) 25 . The overall incidence and unhygienic behaviors revealed suggest the importance of identifying the best solution to address the STH problem in North Sumatra 26 . In parallel with the increased educational activities, footwear deployment has successfully minimized STH infection in endemic locations 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A study in North Sumatra found a significant association between wearing shoes and helminthiasis infection (p = 0.004 and prevalence ratio of 3.195) 25 . The overall incidence and unhygienic behaviors revealed suggest the importance of identifying the best solution to address the STH problem in North Sumatra 26 . In parallel with the increased educational activities, footwear deployment has successfully minimized STH infection in endemic locations 27 .…”
Section: Discussionmentioning
confidence: 99%
“…A systematic review and meta-analysis study done by Strunz et al (2014), as well as a study by Manz et al (2017), reported an important correlation among water, sanitation, hygiene, environment, and exposure to the soil to the prevalence of STHs [12], [13]. The prevalence in this study was lower than the other study done to school children in Singkuang and Sikapas, North Sumatra, by Nasution et al (2019), with a prevalence of 57.1% and 78.1%, respectively [14]. This difference may be caused by the administration of anthelmintic to children in Talawi through a program held by the government in 2019.…”
Section: Discussionmentioning
confidence: 45%
“…Consequently, T-helper1 cells release cytokines and activate the cell-mediated responses, which are effective to fight against intracellular bacteria and protozoa. However, when the allergy-causing protein incorrectly stimulate T-helper2 cell responses, a type 1 hypersensitivity reaction may occur and the allergy responses by IgE may manifest in the skin, sinus, and/or lungs [5,6,14,23,24].…”
Section: Resultsmentioning
confidence: 99%